Death bee comes her - Coco, Nancy (Coco, Nancy. Oregon honeycomb mystery, 2020)
"With her Let It Bee honey boutique buzzing along nicely, life is as sweet as nectar for Wren Johnson--until she takes a morning walk along the Pacific beach with her Havana Brown cat, Everett, and stumbles upon the body of Agnes Snow, the cranky queen of the local craft fairs, stiff as driftwood. More unfortunate? Clutched in the victim's fist is a label from Wren's homemade beeswax-and-honey lip balm. Which makes Officer Jim Hampton focus his dreamy-blue Paul Newman eyes on Wren as suspect number one. With fabulous feline support from Everett, Wren must comb the town for clues and clear her name before someone else gets stung"--